Leveraging Dynamic Capabilities to Overcome Financing Barriers and Drive Sustainability of Solar Social Enterprises in Kenya - Kahinga, Esther; Kitonga, Daniel; Kinyua, Lucy (European Scientific Journal, ESJ, 2025)
This study examined how financing and dynamic capabilities affect the sustainability of solar social enterprises (SSEs) in Nairobi County, Kenya. Against the backdrop of persistent energy access challenges in sub-Saharan Africa, the research aimed to find out how SSEs navigate financing barriers and leverage dynamic capabilities to achieve sustainable growth. Employing a qualitative case study approach, the study draws on in-depth interviews with SSE founders and managers. These were triangulated with business documents and sectoral reports. Key findings reveal that SSEs face significant obstacles in accessing finance, including perceived bias, banks’ risk aversion, and rigorous due diligence requirements. These challenges disproportionately affect locally owned enterprises. The study found entrepreneurial alertness, strategic agility, and resource orchestration as the entrepreneurial dynamic capabilities enabling SSEs to mobilize resources and adapt to market shifts. The study concludes that adapting financing models to local contexts and supporting the development of entrepreneurial dynamic capabilities are vital for the long-term growth of SSEs. Interventions fostering inclusive investment and capacity-building are recommended to advance sustainable growth in Kenya’s dynamic solar sector.